Can veterinary antibiotics affect constructed wetlands performance during treatment of livestock wastewater? - Almeida C.M.R. (2017)
Constructed wetlands (CWs) can be used to reduce various pollutants present in livestock wastewater, such as organic matter, nutrients and metals. Very recently these systems have also been used to remove the so called emergent pollutants. These pollutants can be harmful for both microorganisms and plants, two key players in CWs removal processes. Therefore, the aim of the present work was to assess the influence of emergent pollutants, namely antibiotics, on the removal of pollutants from livestock wastewaters, as antibiotics might decrease CWs performance for the treatment of this type of wastewater. Microcosms (0.4 m × 0.3 m × 0.3 m), simulating CWs, were assembled with Phragmites australis to treat livestock wastewater not doped or doped with 100 μg/L of enrofloxacin and/or of ceftiofur, two antibiotics commonly used in livestock industry. Four different treatments (Control, Enr, Cef and Mix) were tested, each in triplicate. Wastewater was treated during one-week cycle, after which it was removed and replaced by new wastewater (doped or not), in a total of 8 cycles. At weeks 1, 2, 4 and 8 treated wastewater was collected and analysed to determine removal rates of nutrients (ammonia, nitrate, nitrite and phosphate), organic matter (chemical oxygen demand (COD) and biological oxygen demand (BOD)), and solids (including total suspended solids (TSS)), as well as, veterinary antibiotics (enrofloxacin and ceftiofur). High removal rates (up to 90% depending of the parameter) were observed independently of the presence of the veterinary antibiotics, which were also significantly removed from the wastewater. Generally, measured parameters presented values lower than those expressed in the legislation for wastewater discharge into the aquatic environment. Present results indicate that, in tested conditions, the presence of veterinary antibiotics, namely enrofloxacin and ceftiofur, did not influence significantly the biochemical removal processes that occur naturally in CWs during treatment of livestock wastewater, the systems maintaining their performance. Therefore, CWs are a valuable alternative to remove pollutants, including antibiotics, from livestock wastewaters, reducing the impact of this type of effluents into the environment. In addition, this technology can be an efficient/economically viable technology to meet the current wastewater reuse challenges. © 2017 Elsevier